A study on channel coding for 5G / Xu Wei - Xu , Wei (2019)
Due to the interference and fading of mobile communication, errors will occur during the transmission. Therefore, Correction and error detection are very important processes in digital communication systems. They are used to enhance the anti-inference ability of data and improve system reliability. Channel coding is the process of error detection and correction. At present, 3GPP has standardized specifications for channel coding in the 5G NR eMBB scenario, LDPC code is adopted as a channel coding method for data information, and Polar code is adopted for control information encoding. This paper focused on Polar code, specifically described the development and principles of Polar code, and studied Polar code schemes for 5G eMBB specification. In addition, the performances of Polar code under different decoding algorithms and different construction method are simulated and compared. The simulation results show that adding the outer code CRC allows the Polar code to perform error detection during the decoding process and optimize the performance of the polar code. In addition, the SCL decoding algorithm can improve the decoding performance by increasing L. But with the increase of L, the performance improvement becomes smaller and the decoding complexity will be increased. Polar codes generated by different coding construction all can achieve good performance results if combined with the design-SNR construction method. There is no significant performance difference between different coding construction.